Revitalisasi Lahan Terlantar: Ihyā' al-Mawāt karya Syekh Muhammad Arshad Al-Banjari sebagai Model Ekonomi Pesantren di Masyarakat Banjar Abad ke-18 - Sairazi, Abdul Hafiz; Jamalie, Zulfa; Sukarni, Sukarni; Hanafiah, M. (Syariah: Jurnal Hukum dan Pemikiran, 2024)
This study examines the concept of ihyā’ al-mawāt as implemented by Sheikh Muhammad Arshad al-Banjari in 18th-century Banjarese society, focusing on its socio-economic and legal significance. While ihyā’ al-mawāt—the revitalization of abandoned land—is well-documented in Islamic jurisprudence, its practical application by Sheikh Muhammad Arshad remains underexplored. Using a historical approach and a normative legal framework, the research investigates the methods employed in land cultivation, the establishment of communal agricultural systems, and their integration into pesantren institutions. The findings reveal that Sheikh Muhammad Arshad spearheaded land reclamation through the collective efforts of his community, transforming swampy and neglected areas into fertile agricultural land. This initiative not only enhanced the community’s economic welfare but also laid the groundwork for an agro-economic model within pesantren education. The study underscores the enduring relevance of Islamic legal principles in addressing societal challenges and fostering sustainable community development.